2000
DOI: 10.5551/jat1994.7.216
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Low-Density Lipoprotein Oxidation by Astaxanthin

Abstract: Marine animals produce astaxanthin which is a carotenoid and antioxidant. In this study we determined the in vitro and ex vivo effects of astaxanthin on LDL oxidation. The oxidation of LDL was measured in a 1 ml reaction system consisting of increasing concentrations of astaxanthin (12.5, 25.0, 50.0 microg/ml), 400 microM V-70 (2, 2'-azobis(4-methoxy-2, 4-dimethylvaleronitrile)), and LDL (70 microg/ml protein). Astaxanthin dose, dependently significantly prolonged the oxidation lag time (31.5, 45.4, 65.0 min) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(159 citation statements)
references
References 30 publications
1
143
1
7
Order By: Relevance
“…Mutagenesis of H. halophilus was carried out with cells resuspended in minimal G10 medium (glucose 10 g, NH 4 Cl 2 g, FeSO 4 Á7H 2 O 10 mg, Tris base 12 g, K 2 HPO 4 0.49 g, yeast extract 0.1 g, DSM 141 vitamin solution 1 ml and DSM 79 artificial seawater 250 ml in 750 ml tap water) in the presence of 1.0 M NaCl. To 2 ml of the cell suspension, we added and mixed 20 ml ethyl methane sulfonate (Sigma-Aldrich, Steinheim, Germany) vigorously.…”
Section: Random Mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Mutagenesis of H. halophilus was carried out with cells resuspended in minimal G10 medium (glucose 10 g, NH 4 Cl 2 g, FeSO 4 Á7H 2 O 10 mg, Tris base 12 g, K 2 HPO 4 0.49 g, yeast extract 0.1 g, DSM 141 vitamin solution 1 ml and DSM 79 artificial seawater 250 ml in 750 ml tap water) in the presence of 1.0 M NaCl. To 2 ml of the cell suspension, we added and mixed 20 ml ethyl methane sulfonate (Sigma-Aldrich, Steinheim, Germany) vigorously.…”
Section: Random Mutagenesismentioning
confidence: 99%
“…2 Evaluating the pharmaceutical potential of such various carotenoid pigments could be an exciting field of medical research; however, the carotenoid species so far studied for this purpose have been restricted to a small number, including dicyclic carotenoids such as b-carotene, a-carotene, b-cryptoxanthin, zeaxanthin, lutein, canthaxanthin, astaxanthin and fucoxanthin, and an acyclic carotenoid, lycopene. [3][4][5][6] With the exception of those carotenoids that can be isolated from a species of higher plants or be chemically synthesized, it has been difficult to find natural sources that can supply sufficient amounts of these rare carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of natural astaxanthin is several times higher than vitamin E (Naguib, 2000) and 10 times higher than other carotenoids, including zeaxanthin, lutein, ß-carotene, and canthaxanthin (Miki, 1991;Shinidzu et al, 1996). Pre-clinical research has suggested that astaxanthin is a suitable candidate for development as a therapeutic agent for cardiovascular oxidative stress and infl ammation (Pashkow et al, 2008), because it can inhibit the formation of oxidized low-density lipoprotein (LDL) in humans (Iwamoto et al, 2000) and eliminate the lipid peroxidation caused by rofecoxib in cellular membrane models (Mason et al, 2006). Astaxanthin also has neuroprotective effects against retinal damage because of its antioxidant activity (Nakajima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the prevention of LDL oxidation and suppression of OX-LDL-induced cellular effects can have a beneficial effect upon the progression of endothelial injury. The pathophysiological effects of OX-LDL on vascular cells have been well documented; recently, studies have reported that various components in foods can attenuate lipid oxidation [22][23][24][25] . Dietary isoflavones have been suggested to be protective against a range of diseases, including cardiovascular diseases, osteoporosis, and cancer, and have also been reported to alleviate menopausal symptoms in postmenopausal women [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%